The Effectiveness of The Competence of Islamic Religious Extension Workers in Increasing The Religious Diversity of The Community in North Nias Regency - Arnan; Abdullah; Elfi Yanti Ritonga (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to see the effectiveness of Islamic Religious Extension Competence in increasing community religiosity. The method used is qualitative, with the research location in North Nias Regency, from September 2023 to August 2024. Data collection techniques include observation, interviews, and documentation. Research informants comprised the Head of the North Nias Ministry of Religion, the District KUA, the North Nias Pokjapaluh, and representatives from the Muhammadiyah and Nahdlatul Ulama community organisations. Data analysis was carried out through a coding process and integration of data units at the stage of writing the results. The results of the study show: (1) The competence of Islamic religious extension workers includes mastery of religious knowledge, communication skills, technology, and social and psychological skills. They can also design extension programs that suit the community's needs. (2) The communication messages must be relevant, inspiring, touch people's lives, and contain applicable religious motivation. (3) The effects of communication extension include increased understanding of religion, changes in religious attitudes, and social and economic empowerment. Religious instructors have a strategic role in forming a religious, tolerant, and caring society. They can positively influence people's behaviour and quality of life through communication based on moderate Islamic values.